Survivability of low pathogenic (H9N2) avian influenza virus in water in the presence of Atyopsis moluccensis (Bamboo shrimp). (8th November 2017) - Pathak, A. P.; Murugkar, H. V.; Nagarajan, S.; Sood, R.; Tosh, C.; Kumar, M.; Athira, C. K.; Praveen, A.
Summary: Low pathogenic avian influenza virus (LPAIV) exhibits an ecological climax with the aquatic ecosystem. The most widely prevalent subtype of LPAIV is H9N2. Wild aquatic birds being the natural reservoirs and ducks, the "Trojan horses" for Avian Influenza Virus (AIV), can contaminate the natural water bodies inhabited by them. The virus can persist in the contaminated water from days to years depending upon the environmental conditions. Various aquatic species other than ducks can promote the persistence and transmission of AIV; however, studies on the role of aquatic fauna in persistence and transmission of avian influenza virus are scarce. This experiment was designed to evaluate the survivability of H9N2 LPAIV in water with and without Atyopsis moluccensis (bamboo shrimp) for a period of 12 days. The infectivity and amount of virus in water were calculated and were found to be significantly higher in water with A. moluccensis than in water without A. moluccensis . The study also showed that A. moluccensis can accumulate the virus mechanically which can infect chicken eggs up to 11 days. The virus transmission potential of A. moluccensis requires further studies.